Pelatihan Pencatatan Keuangan Sederhana untuk Menumbuhkan Kepedulian Menabung pada Anak-Anak Pesisir Dalam di Desa Bonde, Kecamatan Pamboang, Kabupaten Majene - Nurhidayah Nurhidayah; Dahlia Dahlia (Universitas Prof. Dr. Hazairin, SH, 2019)
Simple Financial Recording Training to Foster Savings Concern for Coastal Children in Bonde Village, Pamboang District, Majene Regency This community service program was aimed to foster awareness and motivation to save early on and to understand the distinction between needs and desires through simple financial records. The training of the simple daily financial recording was carried out in the Meeting Room of Bonde Village Office. Mentoring was also carried out as a continuation of previous training through a simple financial recording module for daily transactions that are commonly carried out by children. The module was given when the training. The mentoring was carried out in one of the houses of Bonde Village residents in Tappa Banua Hamlet, which is a coastal area of ??Bonde Village. The results of the assessment from the training until the last day of mentoring showed that 70% of Bonde village children had understood the simple financial recording of daily transactions that are usually done by children, and they have started to save some of the allowance given by parents/guardians. Others have understood it but have not been motivated to save from an early age.